(3JdNjU efgGL GdhUhd Edi Yde GdGUhds - (3VjGA GdOjf Hf SYO Gddg GdYajais; (3eMeO GdcQOj GdSgQhGfj, efdG RGOg,J (B1070 (3g` ? s ((3CMeO Hf Gdabjg Ydi s)
(3ChdgG (B:s
(3CeG HYO abO GdJeS efi HYV JdNjU cJGH efgGL GdhUhd Edi Yde GdGUhd hSejJg JdNjU efgGL GdhUhd ebOeI GUhd Gdabg s
(3BNQgG (B:s
(3hGWGYI Ghdi GdGeQ ai GdGbVjI hGdSjQI dRhc GdYOd ai bhd YHO GdQMef dYKeGf hSjQI GdTjNjf adGJYGQV hGdGUhd Ydi GdUMjM s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs